Contare il tempo, misurare i corpi: Riflessioni sul protagonismo numerico nel parto ospedaliero - Nicodemo, Annachiara (Antropologia Pubblica, 2024)
The interdisciplinary debate on the effects of medicalisation as experienced by women during pregnancy and childbirth rose during the 70s as part of the reflections of the feminist movement and continued throughout the 80’s with great intensity. A research conducted through direct observation and interviews gives us the chance to partecipate to the debate by questioning the situation of the women hospitalised in public structures of Salta (Argentina). Starting with the premises that bring to the hospitalisation of childbirth which effectively reduce the role of women to that of patients we will explore how certain organisational necessities and at times the arbitrary choices of medical operators substitute women in the decisional process, not recognising them the ability to decide based on how they are feel and on physiological processes. We will especially focus on the effects of labor management when based on protocols which establish the relation between temporal intervals and physical indexes. We will see how time is manipulated during childbirth and how the first contact between mother and child is often delayed to favour bureaucratic necessities. We will also analyse how these phenomena might depend on a particular conception of pain influenced by biomedical rationality. In the end we will underline the risks brought on by a so called humanised assistance to childbirth perpetrated by practices that subordinate women to obstetrical diktats thus favouring an alienation from one’s own feelings and increasing the dependence on medical practices that make the human body virtually indistinguishable form a mere lab specimen.